2019
DOI: 10.2147/ndt.s216079
|View full text |Cite
|
Sign up to set email alerts
|

<p>Evaluating optic nerve diameter as a possible biomarker for disability in patients with multiple sclerosis</p>

Abstract: Background and purposeThe development of new biomarkers for multiple sclerosis (MS) is of paramount importance to improve our ability to predict disease progression and disability. The aim of this study was to evaluate the potential role of the optic nerve diameter (OND) measured by ultrasonography as a biomarker of early disability in patients with relapsing-remitting multiple sclerosis (RRMS).MethodsForty-nine RRMS patients, 23 with a history of optic neuritis (MS-ON) and 26 without a history of optic neurit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The lack of correlation between OND and other disease parameters (disease duration, EDSS) was an unexpected result, since previous studies 15,31,38,39 have shown an inverse correlation between these values, which is to be expected since atrophy is continuous during the course of the disease. Results are, however, conflicting: a study reported no associations between OND and disease duration but showed that OND and EDSS correlate 47 .…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…The lack of correlation between OND and other disease parameters (disease duration, EDSS) was an unexpected result, since previous studies 15,31,38,39 have shown an inverse correlation between these values, which is to be expected since atrophy is continuous during the course of the disease. Results are, however, conflicting: a study reported no associations between OND and disease duration but showed that OND and EDSS correlate 47 .…”
Section: Discussionmentioning
confidence: 76%
“…Studies that investigate this association between optic nerve parameters and conventional MS-related markers report conflicting results and are few in number, mainly focusing on the relationship between the optic nerve sheath diameter, disease parameters and altered brain structure 39 . Bare optic nerve diameter, however, might be more representative of axonal loss, therefore it might reflect structural brain alterations more accurately 15 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For each 1-year increase in the duration of disease, there was an associated decrease of 0.2% in the superficial vascular plexus; and overall, lower density was associated with higher EDSS scores [ 104 ]. In addition, optic nerve diameter and RNFL thickness were significantly lower in individuals with an EDSS score > 2 than in those with an EDSS score ≤ 2 [ 105 ]. Moreover, researchers have shown correlations between diminished RNFL thickness on OCT and MRI volumetric degeneration of the corpus callosum [ 106 ] and brain parenchymal fraction and cerebrospinal fluid (CSF) volume [ 107 ] and correlation between rates of ganglion cell + inner plexiform layer and whole brain atrophy [ 108 ].…”
Section: Methodsmentioning
confidence: 99%